CORRELATION BETWEEN ANTHROPOMETRIC INDICATORS OF OBESITY: BODY MASS INDEX (BMI) AND WAIST CIRCUMFERENCE (WC) IN STUDENT POPULATION FROM NORTH MACEDONIA - Zafirova, Biljana; Zivdainovikj, Julija; Matveeva, Niki; Chadikovska, Elizabeta; Trpkovska, Biljana; Stojanoska, Biljana Bojadgieva; Dodevski, Ace; Paunkoska, Anamarija (Journal of Morphological Sciences, 2022)
The body mass index (BMI) allows for assessing the prevalence of overweight/obesity within a population and determining general obesity. Waist circumference (WC) is a simple and practical anthropometric measure for assessing central adiposity. This study aims to describe the correlation between BMI and WC and examined their significance as indicators of obesity in students. In total, 839 university students aged 18-20 (411 male and 428 female) from Skopje, R. North Macedonia were analyzed. The following anthropometric parameters and indices were considered: weight, height, waist circumference and BMI using a standard protocol. A male had a mean BMI of 24.28 kg/ m 2 and a mean WC of 88.01 cm. Females had a mean BMI of 21.56 kg/m 2 and a mean WC of 74.17 cm. There was a strong positive significant correlation between the BMI and the WC in males (r = 0.81), and a positive correlation in females ( r =0.72). In the identification of overweight/obesity, WC identified significantly more participants than the BMI (255 vs 186). Both the BMI as well as the WC detect people at risk for weight-related diseases, but these results suggest that WC is a better predictor to detect subjects at high risk for abdominal obesity. The determination of obesity based on anthropometric indicators is still an important method for early prevention of serious consequences of obesity among the student population Keywords: Body mass index, waist circumference, student population.